Factor VIII chromogenic assays can be used for potency labeling and postadministration monitoring of N8‐GP. (2nd August 2016) - Pickering, W.; Hansen, M.; Kjalke, M.; Ezban, M.
Abstract : Essentials Chromogenic assays may be less variable than one‐stage clot assays for measuring modified factor VIII. Chromogenic assays were evaluated for N8‐GP potency labeling and postadministration monitoring. There was no significant difference between chromogenic assay kits for measuring N8‐GP potency. Postadministration monitoring of N8‐GP was comparable to turoctocog alfa for all kits tested. Summary: Background: Factor VIII activity (FVIII:C) is commonly measured using one‐stage activated partial thromboplastin time (aPTT)–based clot assays. Chromogenic assays are, however, an alternative, and potency assessment in Europe is performed using chromogenic assays. One‐stage clot assays are in general associated with high variability, and modified FVIII products may add to this variability. FVIII chromogenic assays may be less affected. Objectives: To evaluate available chromogenic assay kits for potency labeling of polyethylene glycol–glycoconjugated turoctocog alfa (turoctocog alfa pegol [N8‐GP]) and to evaluate selected chromogenic kits for postadministration monitoring of N8‐GP using turoctocog alfa (Novoeight ® ) as comparator. Methods: Six FVIII chromogenic assay kits were adapted to the European Pharmacopeia guidelines for potency labeling, including assessment of time to 50% FX activation. Four kits were adapted for postadministration monitoring using an ACL ® TOP 500 analyzer. Severe hemophilia A plasma was spiked with N8‐GP or turoctocog alfa to simulate postadministration samples. The World Health Organization (WHO) 8th International Standard (IS) FVIII concentrate was used as calibrator throughout. In addition, a plasma calibrator was used for postadministration samples. Results: When measuring N8‐GP potency, no significant difference using a 1% significance level was observed between kits. In simulated postadministration samples, all test kits were highly accurate and precise, except at low concentrations, with no significant difference between FVIII:C ( P > 0.05) measured using the different calibrators. However, values obtained using the WHO 8th IS were closer to labeled values. Conclusions: Chromogenic assay kits tested measured consistent FVIII:C for N8‐GP potency and showed comparable results for N8‐GP and turoctocog alfa in simulated postadministration samples.